Oral Nitrate Supplementation Differentially Modulates Cerebral Artery Blood Velocity and Prefrontal Tissue Oxygenation During 15 km Time-Trial Cycling in Normoxia but Not in Hypoxia - Fan, Jui-Lin; Bourdillon, Nicolas; Meyer, Philippe; Kayser, Bengt (Frontiers in Physiology, 2018)
Background: Nitrate is a precursor of nitric oxide (NO), an important regulator of cerebral perfusion in normoxic and hypoxic conditions. Nitrate supplementation could be used to improve cerebral perfusion and oxygenation during exercise in hypoxia. The effects of dietary nitrate supplementation on cerebral haemodynamics during exercise in severe hypoxia (arterial O2 saturation < 70%) have not been explored. Methods: In twelve trained male cyclists, we measured blood pressure (BP), middle cerebral artery blood velocity (MCAv), cerebrovascular resistance (CVR) and prefrontal oxy- and deoxy-haemoglobin concentration (O2Hb & HHb, respectively) during 15 km cycling time trials (TT) in normoxia and severe hypoxia (11% inspired O2, peripheral O2 saturation 66%) following 3-day oral supplementation with placebo or sodium nitrate (0.1 mmol/kg/day) in a randomised, double-blinded manner. We tested the hypothesis that dietary nitrate supplementation increases MCAv and cerebral O2Hb during TT in severe hypoxia. Results: During TT in normoxia, nitrate supplementation lowered MCAv by 2.3 cm/s and increased cerebral O2Hb by 6.8 µM and HHb by 2.1 µM compared to normoxia placebo (p ≤ .01 for all), while BP tended to be lowered (p = .06). During TT in severe hypoxia, nitrate supplementation elevated MCAv (by 2.5 cm/s) and BP (by 5 mmHg) compared to hypoxia placebo (p < .01 for both), while it had no effect on cerebral O2Hb (p = .98), HHb (p = .07) or PETCO2 (p = .12). Dietary nitrate had no effect of CVR during TT in normoxia or hypoxia (p = 19). Conclusion: Our findings indicate that during normoxic TT, the modulatory effect of dietary nitrate on regional and global cerebral perfusion is heterogeneous. Meanwhile, the lack of dramatic changes in cerebral perfusion with dietary nitrate during hypoxic TT alludes to an exhausted cerebrovascular reserve.